Effects of materials and microstructures on pool boiling of saturated water from metallic surfaces - Godinez, Juan C.; Cho, Hanlyun; Fadda, Dani; Lee, Jungho; Park, Seong Jin; You, Seung M. (International Journal of Thermal Sciences, 2021)
Pool boiling experiments using horizontal, flat, and upwards facing aluminum, stainless steel, and copper, heating surfaces are conducted in distilled water. The wettability, measured by the static contact angle (CA), and the critical heat flux (CHF) are found to vary significantly among the three surfaces. The Boehmite treated aluminum, stainless steel, and copper surfaces have a CHF of 1850, 1375, and 1015 kW/m2, respectively. Powder Injection Molding (PIM) and High-Temperature Conductive Microporous Coating (Cu-HTCMC) are also applied on the copper heating surface to create various microstructures, and their pool boiling performances are compared to that of a plain copper surface. The PIM and Cu-HTCMC reduce the contact angle and increase the CHF value. However, the Cu-HTCMC causes an increase in CHF well beyond the expected value, and it is believed to be due to the porous coating structures and reentrant type cavities within the microporous coating.
Keywords: Copper surface; Distilled water; Effects of materials; Heating surfaces; Metallic surface; Microporous coatings; Pool boiling; Powder injection molding; Saturated water; Static contact angle; Critical heat flux; Microporous coating; Pool boiling; Powder injection molding; Wettability